COPPER MICROPARTICLES (MPS Cu) AND CORE-SHELL COPPER@SILVER MICROPARTICLES (MPs Cu@Ag) OBTAINED BY MEANS OF A BUTANOL-GLYCEROL MIXTURE - Echevarria Muñoz, Jezabel (2023)
In this study, the synthesis of Cu MPs and Cu@Ag MPs was carried out using the microwave-assisted polyol method. The reduction of copper acetylacetonate was carried out in a binary mixture of butanol-glycerin solvents with glycerol monostearate (GMS) by microwave heating; accompanied by wet grinding and ultrasonic pulses. The suspension of Cu MPs was coated with silver through galvanic deposition and the transmetalation reaction using a silver nitrate solution, at room temperature and under darkness, thus obtaining Cu@Ag MPs. All microparticles were characterized with XRD, SEM and EDX techniques. With the SEM results, it is deduced that the Cu MPs adopted different morphologies and sizes depending on the butanol-glycerin proportions used during the synthesis, with the butanol-glycerin proportion being 2:3, which allowed obtaining Cu MPs with a more crystalline morphology. average diameter of 3.52 μm. Likewise, the Cu@Ag MPs turned out to be amorphous, forming clusters with average diameters of 0.33μm, 0.52 μm and 0.83 μm when the molar ratios of Cu:Ag 1:1, 2:1 and 3:1 were used. , respectively. The 1:1 Cu@Ag MPs had a more homogeneous coating compared to the others.